Nilai Pendidikan Islam Tradisi Ngrowot dan Implementasinya dalam Materi Modul Ajar SKI Kurikulum Merdeka - Rouf, Muhammad Fatkhu; Nurhalim, Muhammad (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
Abstract A tradition is able to live and survive by teaching noble values that have long been the character of a nation. Not only teaching, but also shaping it, as is the case with education which always strives to create students with noble dedication. But nowadays, traditions are able to disappear not because of a shift in the values contained, but rather the phenomenon of foreign cultural infiltration which little by little erodes the traditions that have been maintained so far. This study aims to find the values of Islamic education stored in the ngrowot tradition of the Nurul Islam Islamic Boarding School in Bnajranegara, and to find out the alignment of these values to education in the form of SKI teaching module material at the madrasah aliyah level. This research is in the form of qualitative research using an ethnographic approach. Sources of data in this study are primary and secondary. Primary data sources were obtained from interviews and observation processes, where interviews were conducted with the caretakers of Islamic boarding schools, administrators and implementers of this ngrowot tradition. Observations were made by looking directly at the ornaments in the ngrowot tradition. Secondary data sources were obtained through dictionaries, scientific journals, and literature related to the ngrowot tradition, as well as documents related to the curriculum in order to align with the values of Islamic education contained in the ngrowot tradition. This study found that there are strong values contained in the ngrowot tradition in the form of aqidah, worship and moral values. This finding can be used as one of the references in the preparation of teaching module material for Islamic religious education subjects, especially in SKI subjects, material for the history of Islamic Nusantara values contained in the E phase of madrasah aliyah with learning outcomes in the form of habituation to a simple, earnest, diligent attitude, and the spirit of respecting traditions. This is none other than because the values contained are directly related to historical material and are in the form of simple implementations that are in accordance with the learning outcomes to be achieved. Keywords: Ngrowot Tradition, Values ​​of Islamic Education, Teaching Modules Abstrak Suatu tradisi mampu hidup dan bertahan dengan mengajarkan nilai luhur yang sejak dahulu menjadi karakter suatu bangsa. Bukan hanya mengajarkan, namun juga membentuknya, sama halnya dengan pendidikan yang selalu berupaya menciptakan peserta didik yang bededikasi luhur. Namun saat ini, tradisi mampu hilang bukan karena pergeseran nilai yang terkandung, lebih kepada fenomena infiltrasi budaya asing yang sedikit demi sedikit menggerus tradisi yang telah dipertahankan selama ini. Penelitian ini bertujuan menemukan nilai-nilai pendidikan Islam yang tersimpan dalam tradisi ngrowot Pondok Pesantren Nurul Islam di Bnajranegara, serta mengetahui keselarasan nilai tersebut terhadap pendidikan dalam bentuk materi modul ajar SKI jenjang madrasah aliyah. Penelitian ini berbentuk penelitian kualitatif dengan menggunakan pendekatan etnografi. Sumber data dalam penelitian ini berupa primer dan skunder. Sumber data primer diperoleh dari proses wawancara dan observasi, dimana wawancara dilakukan dengan pihak Pengasuh Pondok Pesantren, pengurus dan pelaksan tradisi ngrowot ini. Adapun observasi dilakukan dengan melihat langsung ornamen yang ada dalam tradisi ngrowot. Sumber data skunder didapat melalui kamus, jurnal ilmiah, maupun literatur terkait tradisi ngrowot ini, serta dokumen terkait kurikulum guna menyelaraskan dengan nilai-nilai pendidikan Islam yang terdapat pada tradisi ngrowot. Penelitian ini menemukan adanya nilai kuat yang terkandung dalam tradisi ngrowot berupa nilai akidah, ibadah dan akhlak. Temuan ini dapat dijadikan sebagai salah satu referensi dalam penyusunan materi modul ajar mata pelajaran pendidikan agama Islam khususnya dalam mata pelajaran SKI materi nilai sejarah Islam Nusantara yang terdapat pada fase E madrasah aliyah dengan capaian pembelajaran berupa pembiasaan sikap sederhana, sungguh-sungguh, tekun, serta semangat menghargai adat istiadat. Ini tidak lain karena nilai yang terkandung bertautan langsung dengan materi sejarah dan berbentuk implementasi sederhana yang sesuai dengan capaian pembelajaran yang ingin dicapai. Kata Kunci: Tradisi Ngrowot, Nilai Pendidikan Islam, Modul Ajar